2020
DOI: 10.1007/s11920-020-01173-0
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Arousal in Insomnia: Through a Lens of Neuroimaging Studies

Abstract: Purpose of Review Previous research has struggled with identifying clear-cut, objective counterparts to subjective distress in insomnia. Approaching this discrepancy with a focus on hyperarousal and dysfunctional affective processes, studies examining brain structures and neural networks involved in affect and arousal are reviewed and conclusions for an updated understanding of insomnia are drawn. Recent Findings Recent studies found that amygdala reactivity, morphometry and adaptation in insomnia are altered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…Comparing two patients groups showed that although various subcortical regions undergo structural changes in psychophysiological insomnia, it is mainly associated with shrinkage in thalamus, amygdala, and hippocampus. This is in line with the hyperarousal model of insomnia and emotional memory impairment in ID (14,45). This model suggests that ID is characterized by increased arousal at the physiological, endocrine, cognitive or emotional levels and increased amygdala activity (17).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Comparing two patients groups showed that although various subcortical regions undergo structural changes in psychophysiological insomnia, it is mainly associated with shrinkage in thalamus, amygdala, and hippocampus. This is in line with the hyperarousal model of insomnia and emotional memory impairment in ID (14,45). This model suggests that ID is characterized by increased arousal at the physiological, endocrine, cognitive or emotional levels and increased amygdala activity (17).…”
Section: Discussionsupporting
confidence: 85%
“…The amygdala plays a key role in processing negative emotional arousal and fear-inducing stimuli and therefore is involved in the hyperarousal model of ID (14,45). Gong et al also reported atrophy in the left superficial and right basolateral nucleus of amygdala, the association of insomnia severity with shape of the right centromedial nucleus, and the link between anxiety and shape of the basolateral nucleus of amygdala (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroimaging studies are also supporting this view. As recently summarized by Schiel et al (2020), insomnia is related to altered amygdala reactivity, morphometry, and adaptation. Moreover, insomnia is associated with aberrant connectivity in the default mode network, alterations in the salience network associated with hyperarousal, maladaptive emotion regulation, and disturbed integration of emotional states.…”
Section: The Interplay Between Sleep and Emotion: What Role Do Cognitmentioning
confidence: 99%